A utilização da caderneta de saúde da pessoa idosa na atenção primária: um olhar na formação em saúde - Ramos, Luiza Vargens (2019)
Health spaces such as UBS are considered non-formal teaching environments. Recognizing and valuing the professionals ' previous knowledge to analyze what is already known and what is needed to learn to improve the integral care of the elderly has been the subject of research in education and health. The elderly person's health booklet (CSPI) is an instrument for technical training and can contribute to institutional changes or orientation in the health service. Among the challenges of the implementation of the CSPI in the SUS, we highlight the lack of training and adherence by professionals, the lack of information about the booklet and difficulties to fill the professionals. Therefore, understanding how the training processes happen and what health professionals perceive in relation to CSPI in primary care can contribute to the formulation of new strategies for implementing this instrument. Therefore, this dissertation aimed to investigate the use of the booklet by health professionals as an instrument of technical training in the health care of the elderly in the municipality of Gurupi, TO. This is a cross-sectional descriptive observational study with a mixed (quanti-qualitative) approach. The sample consisted of 60 health professionals with bonds, in family health units. To obtain the data, a questionnaire consisting of open and closed questions was used, divided into three modules: the first with socio-economic and labor issues, the second with knowledge and difficulties of the professionals with the CSPI, and the third with Evaluation of teaching strategies in primary care. The results showed a heterogeneous process of implantation and utilization of the CSPI in the health units, some are in the process of implementation, but with training difficulties and others use the CSPI in the outdated version. We did not find in our municipality the implementation of the latest version of the instrument. Thus, we consider that there is a need for permanent discussions and trainings so that the workspaces are spaces for identifying professionals difficulties and exchanging knowledge, increasing the construction of knowledge and efficacy of Units to cope with the complexities of the elder.